2020
DOI: 10.1186/s13756-020-00791-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for sepsis by carbapenem resistant Gram-negative bacilli in adult critical patients in Rio de Janeiro: a case-case-control design in a prospective cohort study

Abstract: Background Studies have investigated risk factors for infections by specific species of carbapenem-resistant Gram-negative bacilli (CR-GNB), but few considered the group of GNB species and most of them were performed in the setting of bacteremia or hospital infection. This study was implemented to identify risk factors for sepsis by CR- and carbapenem-susceptible (CS) GNB in intensive care unit (ICU) patients to improve management strategies for CR-GNB sepsis. Methods W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…Through nationwide surveillance in Taiwan since 2011, an increased resistance to carbapenem has been demonstrated in A. baumannii , K. pneumoniae, and P. aeruginosa from 69.8 to 75.3%, 10.5 to 44.4% and 17.7 to 22.6%, respectively 23 . Previous studies have demonstrated that risk factors, such as carbapenem consumption, LOS, diabetes mellitus, multiple lobar involvement, and prior exposure to antimicrobial therapy, are associated with the acquisition of CRGNB infection 24 27 . Moreover, the mortality rate of nosocomial pneumonia caused by CRGNB is also high.…”
Section: Discussionmentioning
confidence: 99%
“…Through nationwide surveillance in Taiwan since 2011, an increased resistance to carbapenem has been demonstrated in A. baumannii , K. pneumoniae, and P. aeruginosa from 69.8 to 75.3%, 10.5 to 44.4% and 17.7 to 22.6%, respectively 23 . Previous studies have demonstrated that risk factors, such as carbapenem consumption, LOS, diabetes mellitus, multiple lobar involvement, and prior exposure to antimicrobial therapy, are associated with the acquisition of CRGNB infection 24 27 . Moreover, the mortality rate of nosocomial pneumonia caused by CRGNB is also high.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of mechanical ventilation and the length of time the tube is present constitute the main extrinsic risk factors for the development of respiratory tract infections. 14,40,41,42,21,32,22 As well as the greater risk of infection by resistant bacteria. 42 In addition to the risk factors directed to specific sites, other risk factors stood out as predictors of more frequent infections, such as length of stay in the ICU 14,34,39,17,34,39,17,33,18,20,21,22 , use of invasive devices 44,45,25,30,31,18,19,20,28,46 , advanced age 17,18,19,20,21,22 , comorbidities: diabetes mellitus 14, 47,30,48,49,50 , arterial hypertension 27 , chronic obstructive pulmonary disease 32 and smoking.…”
Section: Risk Factors For Respiratory Tract Infectionmentioning
confidence: 99%
“…14,40,41,42,21,32,22 As well as the greater risk of infection by resistant bacteria. 42 In addition to the risk factors directed to specific sites, other risk factors stood out as predictors of more frequent infections, such as length of stay in the ICU 14,34,39,17,34,39,17,33,18,20,21,22 , use of invasive devices 44,45,25,30,31,18,19,20,28,46 , advanced age 17,18,19,20,21,22 , comorbidities: diabetes mellitus 14, 47,30,48,49,50 , arterial hypertension 27 , chronic obstructive pulmonary disease 32 and smoking. 51 The identification of risk factors for infection in patients makes it possible to direct interventions with more assertive multidisciplinary approaches to achieve best practices and contribute to reducing the outcomes of HAI indicators 10 .…”
Section: Risk Factors For Respiratory Tract Infectionmentioning
confidence: 99%
“… 4 , 6 , 11 Actively surveillance and infection control measures dramatically decreased CRE colonization thereby reducing mortality. 13–15 Importantly, BSI caused by CRNFB should be a matter of great concern, since limited data suggested that NFB displayed a greater carbapenem resistance rate as well as a higher mortality rate than CRE, 16 , 17 30-day mortality rate up to 45%–100%. 18–20 Our previous data also demonstrated a higher mortality rate of CRNFB BSI in HM patients compared to CRE (44.7% vs 36.0%, respectively).…”
Section: Introductionmentioning
confidence: 99%